Plasma Angiotensin II Levels In Women With Type 2 Diabetes With Or Without Hypertension - Etra Ariadno (Acta Interna The Journal of Internal Medicine, 2012)
ABSTRACT Background. Hypertension is a major risk for the development and progressivity complication of macro and microvascular of diabetes mellitus. Renin-angiotensin-aldosteron system (RAAS), insulin resistance, endothelial dysfunction and autonomic nervous dysfunction play an important part in the pathogenesis of hypertension and type 2 diabetes mellitus. In RAAS, increased angiotensin II constricts arterioles, raises total peripheral resistance and blood volume. The rise in intravascular volume increases risk of hypertension. Glucotoxicity or hyperglycemia in type 2 diabetes mellitus can increases angiotensin II levels.Aim. To evaluate plasma angiotensin II levels in type 2 diabetes mellitus women with or without hypertension.Methods. Cross sectional design was conducted on subjects from outpatients’ women with type 2 diabetes mellitus at endocrinology clinic, Dr. Sardjito General Hospital, Yogyakarta. Hypertension was assessed using criteria from Seventh Joint National Committee (2003). ELISA sandwich method was used to measure plasma angiotensin II levels from blood vein. Differences between groups were compared by student’s unpaired t-test and Mann-Whitney test.Results. Among 60 subjects, there are 30 with hypertension (50%) and 30 without hypertension (50%). Mean age were 54.11 ± 3.36 years old. Plasma angiotensin II levels was higher in women with type 2 diabetes mellitus with hypertension than without hypertension although significance was not reached (0.30 ± 0.15 ng/mL vs. 0.28 ± 0.18 ng/mL, p= 0.93).Conclusion. The plasma angiotensin II levels are not significantly different between type 2 diabetes mellitus women with or without hypertension. Key words: hypertension, plasma angiotensin II, type 2 diabetes mellitus, women